RUANG PASCAKOLONIAL DALAM DOCTOR WOOREDDY’S PRESCRIPTION FOR ENDURING THE ENDING OF THE WORLD KARYA COLIN JOHNSON - Eni Purwanti (POETIKA, 2014)
This writing discusses one of Colin Johnson or Mudroroo’s novel entitled Doctor Wooreddy’s Prescription for  Enduring the Ending of the World to reveal colonial construction of space in Van Diemen’s Land and to analyze postcolonial spatial responses emerged as a form of negotiation toward the contested space. Postcolonial theory of space is applied to discuss the issues. The result of the discussion shows that the White colonial in Van Diemen’s Land constructed their colonial space by arousing chaos and establishing order and borders to create a fixed boundary. The constructed space is proven fail to achieve its goal by arousing some self contradictions which make it lays as merely a utopia. Chaos appears within the order or structure of the space followed by violations trespass the colonial borders to create a new order or structure of a post-space. Post-space within its process will be a new space with new possibilities of chaos, thus, space will be continuously constructed and deconstructed as a form of spatial response of postcolonial space. Keywords: Colonialism, Postcolonial Space, Spatial Response, Aborigines.